The Therapeutic Dimension of Christian Benevolence: Exploring the Link between Poverty Alleviation and Mental Well-Being in the Nigerian Church (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
Poverty remains a persistent social reality in Nigeria, significantly affecting individuals' mental, physical, and spiritual well-being. Nigerian Christian benevolence has often focused on meeting physical needs. The Nigerian church has historically responded to poverty through various benevolent practices, including food distribution, skill acquisition schemes, educational sponsorship, and microfinance interventions. However, the therapeutic dimension of such Christian benevolence, particularly its capacity to contribute to mental well-being, remains underexplored within empirical and theological discourses. Thus, this paper investigates how Christian poverty alleviation practices within Nigerian churches improve the mental health of beneficiaries. Employing a qualitative methodology, the paper utilises analytical, critical, and expository methods of data interpretation. Drawing from testimonies of beneficiaries across selected churches in Lagos and supported by participant observation, the paper identifies reduced anxiety, renewed hope, an enhanced sense of belonging, and improved self-worth as common outcomes among recipients of church-based benevolence. Additionally, spiritual counselling and prayer provided during welfare activities often reduce feelings of isolation, hopelessness, and despair among recipients. The study concludes that Christian benevolence, while addressing physical poverty, plays a therapeutic role in supporting mental well-being in low-resource communities when it integrates economic support with spiritual and social care. The paper debunks secularistic arguments which claim that the church is insignificant in contemporary times. The paper advances the discourse on the nexus between religion and mental health in Africa and offers a model for faith-based poverty alleviation initiatives that meet material and psychological needs. This intersection is critical for scholars in practical theology, religious studies, and mental health, as well as policymakers engaging faith communities in poverty and mental health interventions.